Genetic Types and Catagenesis of Paleozoic Oils in the Southeast of Western Siberia (Russia); 29th International Meeting on Organic Geochemistry, IMOG 2019 - Fadeeva S. V. Svetlana Vasilievna; Goncharov I. V. Ivan Vasilyevich; Oblasov N. V. Nikolay Vladimirovich; Veklich M. A. Maksim Aleksandrovich; Samoilenko (Samoylenko) V. V. Vadim Valerievich; Zherdeva A. V. Aleksandra Valerievna; Litvinova A. E. Anzhela Evgenjevna (2019, 2019)
Title screen